THE PRINCIPLES FOR IJTIHÂD IN RESPONSE TO THE CONTEMPORARY PROBLEMS - Fauzi Fauzi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2018)
Abstract: This article focuses on the qualifications a mujtahid should meet in responding to current problems in the modern era. The author argues that the quality of hadith is influential in legal deduction of taklîfî rulings which might fall under the category of: wâjib, sunnah, mubâh, harâm and makrûh. Mujtahid is also required to be able to understand consensus arguments (ijmâ‘) amongst scholars so that no mujtahid can exercise their legal deduction which contradicts with the existing consensus. It is also urgent that a mujtahid understand the position of the analogy both theoretically and practically and understand the differences between the methods of ijtihâd starting from the phase of revelation, the period of Companion of the Prophet to the time of the legal school of thoughts. On top of the above-mentioned conditions, a mujtahid would only be able to respond to contemporary issues when he or she has an adequate understanding of the maslahah or what is popularly known as public interest in Islamic legal discourse.Abstrak: Rambu-rambu Perumusan Hukum dalam Merespon Masalah Kontemporer. Artikel ini menfokuskan pada standar persayaratan yang harus dipenuhi seorang mujtahid dalam merespon masalah kekinian di era modern. Penulis mengemu-kakan bahwa bahwa kualitas hadis berpengaruh dalam menyimpulkan hukum taklîfî yang berada pada tataran: wâjib, sunnah, mubâh, harâm dan makrûh. Mujtahid juga dipersyaratkan mampu memahami argumen konsensus (ijmâ’) antara ulama sehingga tidak ada mujtahid yang melakukan istinbâth hukum yang berlawanan dengan konsensus yang ada, memahami kedudukan analogi baik secara teoritis maupun praktis dan memahami perbedaan metode ijtihâd lintas masa mulai fase turunnya wahyu, masa sahabat, masa tabiin dan masa mazhab. Di atas semua persyaratan tersebut di atas, seorang mujtahid hanya akan mampu merespon isu-isu kontemporer ketika memiliki pemahaman yang memadai tentang teori maslahah atau public interest.Keywords: Islamic law, ijtihâd, mujtahid, contemporary issues